The Correlation between Self-confidence and English Speaking Achievement - Ari Wiryadi Joni, Dewa Ayu; Istri Yudhi Pramawati, Anak Agung; Intan Setiasih, Ni Kadek (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2023)
The primary objective of this study is to investigate whether there is a significant correlation between self-confidence and speaking achievement of the eighth-grade students of SMPN 3 Mengwi. The subjects were 32 subjects consisting of 16 males and 16 females. The design was the correlational research design. In collecting the data of this research, two instruments which were used such as self-confidence questionnaire consisting of 30 items and monologue speaking test. The data was analyzed using Pearson Product Moment Correlation. This study was designed to test the research hypothesis that is there is a positive correlation between self-confidence and speaking achievement. Hypothesis tests are computed using SPSS 25 version for Windows. Referring to the data, the study concluded that there was a positive and significant correlation between the eighth-grade students’ self-confidence in SMPN 3 Mengwi and their performance in speaking